Previously Unreported Chromosomal Aberrations of t(3;3)(q29;q23), t(4;11)(q21;q23), and t(11;18)(q10;q10) in a Patient with Accelerated Phase Ph+ CML. (22nd February 2014) - Aydin, Cigdem; Cetin, Zafer; Salim, Ozan; Yucel, Orhan Kemal; Undar, Levent; Berker Karauzum, Sibel
Abstract : Chronic myelogenous leukemia (CML) is a clonal hematological disorder, which is characterized by the presence of the classical or variant Philadelphia translocations. During the progression to blastic phase of the disease secondary chromosomal abnormalities may emerge. Such secondary chromosomal abnormalities are nonrandom, the more frequent ones being trisomy 8 and 19, supernumerary i(17q), and extra Philadelphia chromosomes. Furthermore, a minor percentage of the patients may acquire different secondary chromosomal abnormalities including translocations between other chromosomes. We report here a patient with Ph+ CML presenting secondary chromosomal abnormalities including t(4;11)(q21;q23), t(3;3)(q29;q23) and t(11;18)(q10;q10) during the course of CML progression.